The Relationship Between Self-Confidence Levels and Forward Roll Skill in Students at Elementary School - Miftado Akhmad Ridhiaz; Eki Aldapit; Yopi Hutomo Bhakti; Mela Suhariyanti (Universitas Negeri Semarang, 2026)
This research is motivated by the importance of mastering basic movement skills in elementary school physical education, especially in the forward roll floor gymnastics material which demands physical and psychological readiness of students. The purpose of this study was to determine the relationship between self-confidence and forward roll motor skills among sixth-grade students at State Elementary School 02 Rejosari. The forward roll is a floor gymnastics skill that requires a high level of complexity and mental and physical readiness from students. This study used a quantitative correlational approach with a cross-sectional research design. The population of this study consisted of all sixth-grade students at State Elementary School 02 Rejosari who had learned floor gymnastics material. The sample consisted of 20 students selected using purposive sampling. The research instruments were a self-confidence questionnaire with 15 statements and an observation sheet for assessing the technical aspects of the forward roll. Data analysis was performed using the Pearson product-moment correlation test with the help of SPSS 25 software. Based on the research results, the correlation value was 0.624, with a significance of 0.003 (p<0.05), which means that students' self-confidence and forward roll skills have a positive and significant relationship that is classified as strong, so that the higher the level of self-confidence, the better the students' forward roll skills. The results of this study prove that psychological aspects in physical education learning are very influential and have implications for teachers to train self-confidence in floor exercise learning.